Indicators of quality teaching in intensive behavioral intervention: a survey of parents and professionals - Perry, Adrienne; Prichard, E. Alice; Penn, Helen E. (Behavioral interventions, 2006)
Intensive Behavioral Intervention (IBI) is being used extensively with children with autism. It is widely accepted that a large quantity of IBI is necessary to maximize children's outcomes, but outcomes remain variable and one reason for this is likely related to the quality of intervention children are receiving. There is little empirical evidence regarding the nature and measurement of quality IBI. This paper presents results of a survey examining the views of parents and professionals about quality IBI and how it should be measured. Parents rated the importance of 11 IBI characteristics and professionals indicated whether these characteristics should be measured objectively or subjectively. All respondents selected three characteristics they thought most important and answered open‐ended questions about: additional quality indicators and IBI programming issues for which empirical evidence is needed. Parental ratings supported the importance of virtually all the suggested characteristics. Professional results emphasized the importance of objective measurement. The most frequently selected indicators of high quality teaching across groups were: creating generalization opportunities, administering reinforcers of the appropriate type, and using effective/appropriate behavior management strategies. There were interesting differences across groups and many valuable suggestions about additional indicators of quality and empirical questions of interest. Copyright © 2006 John Wiley & Sons, Ltd.